Jewish legal regulation documents from Lucena in the 11th century - García Arévalo, Tania María; Cano Pérez, María José (Cuadernos de Historia del Derecho, 2016)
The aim of these pages is to offer a view on the Jewish regulation of Lucena (Cordoba) in the 11th century. Through the legal texts originating from this place, which were conserved in the Cairo Genizah and later guarded at the Bodleian Library in Oxford, it is possible to observe the legal procedure of this group in relation to two essential issues: its consideration of dhimmis, due to its belonging to the ’ahl al-Kitāb or ‘people of the Book’ category, and the internal regulation of the community according to the problems emerged in it. In this article, therefore, the more frequent legal matters derived from the litigations conserved from this city until these dates will be studied.
Keywords: Lucena; al-Yussana; 11th century; Middle Ages; Jews; al-Andalus; ḏimma; Muslims; regulation; documents; agreements